Um sistema de criptografia de chave pública chamado ElGamal - Silva, Paulo Sérgio Lopes da (2015)
In this paper we will address public key cryptosystem ElGamal. In the first chapter we present all the mathematical concepts addressed, especially the index. In the second chapter we will talk about the system concepts studied in this paper, historical and relevant facts that were important for its implementation. The coding and encoding method in this cryptosystem is presented in the third chapter. In the fourth and fifth chapter we finish presenting a didactic proposal to include encryption in the regular teaching mathematics.